1989
DOI: 10.1002/1097-0142(19890915)64:6<1218::aid-cncr2820640609>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Small bore catheter drainage and sclerotherapy for malignant pleural effusions

Abstract: The accumulation of large amounts of fluid in the pleural space is a common sequela of disseminated carcinomatosis. Traditional management has included therapeutic thoracentesis or the placement of a large bore chest tube for drainage with the subsequent installation of a sclerosing agent in an attempt to achieve pleural symphysis. An evaluation of all patients treated in this manner during a 4-year period was undertaken to assess the degree of success obtained with a large bore standard chest tube versus a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…Most commonly, pleurodesis is performed via a standard tube thoracostomy. However, some studies have reported similar success rates with small-bore (3-5 mm) catheters [120][121][122][123][124][125]. Ideally, the chest tube is directed posteriorly toward the diaphragm.…”
Section: Chemical Pleurodesismentioning
confidence: 99%
“…Most commonly, pleurodesis is performed via a standard tube thoracostomy. However, some studies have reported similar success rates with small-bore (3-5 mm) catheters [120][121][122][123][124][125]. Ideally, the chest tube is directed posteriorly toward the diaphragm.…”
Section: Chemical Pleurodesismentioning
confidence: 99%
“…Studies using small bore catheters (8-14 F) have reported similar success rates to those using large bore tubes, and small bore catheters are better tolerated and associated with less discomfort. [9][10][11][12] In the only controlled randomised study published to date, no significant diVerence was seen in the pleurodesis success rate but larger randomised studies are required to confirm these results. 13 A further potential advantage of the small bore catheter is in the area of ambulatory treatment of malignant eVusions.…”
Section: Size Of Drainage Tubementioning
confidence: 99%
“…The accurate detection of mediastinal lymph nodes in oesophageal cancer had obvious implications for patients with lung cancer, and the role of EUS in lung cancer was first described in Japan in 1988. 8 Further work confirmed the superior accuracy of EUS in the nodal staging of lung cancer compared with computed tomographic (CT) scanning, 9 although EUS is not yet used routinely in the preoperative staging of lung cancer in the UK.…”
mentioning
confidence: 97%
“…MPE constitutes approximately 30% -60% of all pleural fluids. [1][2][3] Symptomatic treatment in MPE is possible with pleurodesis and there are various catheter and drainage systems which are used for the purpose of drainage and pleurodesis.…”
Section: Introductionmentioning
confidence: 99%